Q&A - Ask Doubts and Get Answers

Sort by :
Clear All
Q

find and correct the errors in the following mathematical statements

Q21)

\frac{7x +5}{5} = 7x

Our L.H.S. is    R.H.S. Correct statement is  

find and correct the errors in the following mathematical statements

Q20)

\frac{4 x + 5 }{4x } = 5

Our L.H.S. is     R.H.S.   Correct statement is 

find and correct the errors in the following mathematical statements

Q19) 

\frac{3}{4x +3}= \frac{1}{4x }

Our L.H.S. is     R.H.S. Correct statement is 

find and correct the errors in the following mathematical statements.

Q18)

\frac{3 x }{3 x +2 } = 1/2

Our L.H.S.      R.H.S. = 1/2 It can be clearly observed that L.H.S is not equal to R.H.S So, the correct statement is,  

Find and correct the errors in the following mathematical statements.

Q17)

\frac{3 x ^2 + 1 }{3 x ^2 } = 1+1 = 2

Our L.H.S.  is      R.H.S. = 2 It is clear from the above stattement that L.H.S. is not equal to R.H.S. So, correct statement is   

Find and correct the errors in the following mathematical statements.

Q16)

\frac{3 x ^2}{3 x ^2 } = 0

Our L.H.S.  is           R.H.S. = 0 It is clear from the above that L.H.S. is not equal to R.H.S. So, correct statement  is    

 

Find and correct the errors in the following mathematical statements.

Q15)

(a - 4 ) ( a - 2 )= a ^2 - 8

Our L.H.S. is (a - 2) (a - 4)                      =                       =     R.H.S. Correct statement is  (a - 2) (a - 4)  =  

Find and correct the errors in the following mathematical statements.

Q14)

( a + 4 ) ( a +2 ) = a ^ 2 + 8

Oue L.H.S. is  (a + 4)(a + 2)                      =                      =      R.H.S. Correct statement is   (a + 4)(a + 2)  = 

Find and correct the errors in the following mathematical statements.

Q13)

( 2a +3b ) ( a-b) = 2 a ^2 - 3 b^2

Our L.H.S. is  (2a + 3b)(a -b)                    =                     =       R.H.S. Correct statement is  (2a + 3b)(a -b) = 

Find and correct the errors in the following mathematical statements

Q12)

( z+5 ) ^2 = z^2 + 25

Our L.H.S. is                            =                                         using                          =       R.H.S. Correct statement  is     =     

Find and correct the errors in the following mathematical statements

Q11) 

( y - 3 ) ^ 2 = y ^ 2 -9

Our L.H.S.  is                           =                                                                 using                             =   R.H.S. Correct statement  is    = 

 find and correct the errors in the following mathematical statements

Q10) Substituting x = - 3 in

(c)

x ^2 + 5 x \: \: gives \: \: ( -3 ) ^ 2 + 5 ( -3 ) = -9-15 = -24

We need to  Substitute  x = - 3 in                                                        =                                                        = 9 - 15                                                      = - 6     R.H.S  Correct statement is   Substitute  x = - 3 in      gives -6

find and correct the errors in the following mathematical statements

Q10) Substituiting x = -3 in

(b)

x ^2 -5 x + 4 \: \: gives \: \: ( -3)^2 - 5 ( -3 ) + 4 = 9 - 15 + 4 = -2

We need to substitute x = -3 in                                                                                         so the given statement is wrong                               Correct statement is     

Find and correct the errors in the following mathematical statements

Q10) Substituting x = -3 in 

a)

x ^ 2 + 5 x + 4 \: \: gives \: \: ( -3 ) ^ 2 + 5 ( -3 ) + 4 = 9 + 2 + 4 = 15

  We need to substitute  x = -3 in              so the given statement is wrong Correct statement is   

Find and correct the errors in the following mathematical statements 

Q9

( 3x +2 )^2 = 3 x ^2 + 6x + 4

LHS IS                                            usnig                               RHS IS Correct statement is    

Find and correct the errors in the following mathematical statements 

Q8. 

( 2 x)^2 + 5 x = 4 x +5x = 9 x

Our L.H.S. is          R.H.S. = 9x It is clear from the above that L.H.S. is not equal to R.H.S. So, the correct  statement is     

 Find and correct the errors in the following mathematical statements

Q7

( 2x )^2 + 4 ( 2x ) + 7 = 2 x^2 + 8 x +7

Our L.H.S. is      R.H.S.  It is clear  from the above that L.H.S. is not equal to R.H.S. So, correct statement is 

Find and correct the errors in the following mathematical statements 

Q6.

3 x +2 x = 5 x ^2

Our L.H.S. is      R.H.S. =  It is clear from the above that L.H.S. is not equal to R.H.S. So, correct statement is  

Find and correct the errors in the following mathematical statements 

(Q5)\ 5 y + 2y + y - 7y = 0

Our L.H.S. is    R.H.S. = 0 IT is clear from the above that  L.H.S. is not equal to R.H.S. So, Correct statement is  

Find and correct the errors in the following mathematical statements 

(4)x + 2x + 3x = 5x

Our L.H.S.    R.H.S.  It is clear from the above that L.H.S. is not equal to R.H.S. So, correct statement is  
Exams
Articles
Questions